World Development Report 2019 : The Changing Nature of Work - World Bank (Washington, DC: World Bank, 2018)
Work is constantly reshaped by technological progress. New ways of production are adopted, markets expand, and societies evolve. But some changes provoke more attention than others, in part due to the vast uncertainty involved in making predictions about the future. The 2019 World Development Report will study how the nature of work is changing as a result of advances in technology today.